Literature Review of Public Sector Transformational Leadership - Fatolosa Hulu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This article describes the need for transformational leadership in government. This is caused by the occurrence of moral degradation of the nation which undermines the joints of the life of the nation and state. The development of corruption, collusion, and nepotism as evidence of the severity of the moral degradation of the Indonesian nation, which almost plunged the Unitary State of the Republic of Indonesia (NKRI) into the brink of collapse. The presence of several reformist leaders who characterize transformational leadership in this reformation era, especially in the public sector, provides fresh air for the leadership crisis and public distrust of their leaders. These transformational leaders have a high spirit of altruism and philanthropy. They are able to show their concern for the people they lead, even though they face challenges and threats from various parties that are contrary to their political direction. In this study, the researcher used the library research method. The material used in compiling this article uses reading materials and secondary data. The collected material, data and information are then compiled and analyzed, so as to produce conclusions that can be accounted for. This article concludes that transformational leadership in the public sector is very much needed in Indonesia, especially in the regions.